2012
DOI: 10.1038/sc.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative affect in individuals with spinal cord injuries

Abstract: Study design: Participants with spinal cord injuries (SCIs) and healthy controls completed standardized questionnaires assessing depression level, positive and negative affect, and personality traits. Objectives: To identify the specific characteristics of emotional experiences affected by spinal cord injury. Setting: A Canadian rehabilitation center. Individuals with SCIs were recruited from a list of patients who had volunteered to participate in studies being conducted by the SCI clinic. Healthy controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous research has discussed the impact of SCI on psychological and emotional health. [8][9][10][11] In this study, participants identified a positive effect on psychological and emotional health as a quality outcome of employment. An idea noted by many participants was that work kept them busy, helping them avoid depression, addiction, and morbid thinking.…”
Section: Theme: Psychological -Emotional Healthmentioning
confidence: 79%
“…Previous research has discussed the impact of SCI on psychological and emotional health. [8][9][10][11] In this study, participants identified a positive effect on psychological and emotional health as a quality outcome of employment. An idea noted by many participants was that work kept them busy, helping them avoid depression, addiction, and morbid thinking.…”
Section: Theme: Psychological -Emotional Healthmentioning
confidence: 79%
“…The PANAS has convergent validity when correlated with the Depression and Anxiety Stress Scale [ t (986) = 7.523, p < 0.001] and the Hospital Anxiety and Depression Scale [ t (737) = 7.667, p < 0.001] (Crawford and Henry, 2004 ). PANAS has been used in both ABI (e.g., Juengst et al, 2014 ) and SCI research (Salter et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whilst the Hospital Anxiety and Depression Scale was most frequently used (with demonstrated validity in people with SCI [24]), the Beck Depression Inventory has also been found to perform well in SCI populations [25]. However, despite the Positive and Negative Affect Scale being utilised in prior work with people with SCI, this measure has not been validated in this group [26]. Pain-related outcomes were also frequently assessed, with four studies utilising the Brief Pain Inventory [6,20,22,23] (an established reliable and valid measure of pain-related interference in people with SCI and pain [27]).…”
Section: Intervention Characteristicsmentioning
confidence: 99%